An introduction to second language acquisition research - Larsen-Freeman, Diane; Long, Michael H. (b, 1991)
Understanding how people learn and fail to learn second and foreign languages is increasingly recognised as a critical social and psycholinguistic issue. This book provides a synthesis of empirical findings on second and foreign language learning by children and adults, emphasising the design and execution of appropriate research.
Includes bibliographical references and index.
Keywords: v; Foreign language skills -- Research. -- Acquisition